Steel Statically Uncertain Transverse Frames Probabilistic Calculation - Chichulina, Kseniia; Chichulin, Viktor; ., . (International Journal of Engineering and Technology, 2018)
The aim of the work is probabilistic calculation and evaluation of steel statically uncertain frames reliability parameters and recommendations development for reducing their material content by controlling the reserves of the load bearing capacity of the.A method for evaluating the reliability parameters of steel statically uncertain frames by all able-bodied statens is developed. LogicalÂ  probabilistic methods of statically uncertain systems work are used. The probability estimation method of statically uncertain systems failure based on the boundary equilibrium method, taking into account the correlation of individual destruction schemes, is obtained. The method of calculating the significance and contribution of individual frame elements and their influence on the system failure probability as a whole is proposed. The practical method of designing steel statically unidentified frames with the use of steel statically uncertain constructions reliability coefficient Î³s is offered. The scientific novelty of the work is to develop a scheme for determining frames failure probability by estimating the working capacity. In particular, the fragile and plastic fracturing failures of the frame section are considered. The algorithms for calculating the steel frames failure probability are determined by the probabilistic method of graphical equilibrium. The steel frame separate elements significance indexes are determined. The numerical experiment on the developed programs on a PC is presented for estimation of steel frames failure probability of various sections. the of of steel statically uncertain constructions reliability coefficient Î³s is proposed for usage.The practical value is more complete consideration of the structures and the probabilistic nature of strength and load, the use of the reliability coefficient. The possibilities of obtaining more economical frames in the design of new ones as well as reconstruction of existing buildings and facilities are identified. Based on the proposed methodology, algorithms and developed programs on the PC for the probabilistic calculation of steel statically uncertain frames for various purposes are compiled.Â Â